2013
DOI: 10.1016/j.febslet.2013.04.046
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 is a natural inhibitor of the CXCL12–CXCR4 signaling axis

Abstract: Edited by Beat ImhofKeywords: Chemokine CXCL14 CXCL12 CXCR4 a b s t r a c t Activation of the CXCL12-CXCR4 pathway is crucial for the migration of hematopoietic stem cells, various immune cells, and malignant tumor cells. Here, we show that another CXC chemokine, CXCL14, specifically binds to CXCR4 with high affinity and inhibits the CXCL12-mediated chemotaxis of human leukemia-derived cell lines and CD34 + hematopoietic progenitor cells. Thus, CXCL14 functions as a natural inhibitor of CXCL12. Our observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 26 publications
5
98
0
Order By: Relevance
“…MSCs secrete anti‐inflammatory, immunosuppressive, anti‐apoptotic and proangiogenic factors 29, 30. MSC‐conditioned medium increases capillary density and preserves cardiac function 31. Recent clinical trials have suggested that secretion of paracrine factors may be the underlying mechanism responsible for the improvement in outcomes 4.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs secrete anti‐inflammatory, immunosuppressive, anti‐apoptotic and proangiogenic factors 29, 30. MSC‐conditioned medium increases capillary density and preserves cardiac function 31. Recent clinical trials have suggested that secretion of paracrine factors may be the underlying mechanism responsible for the improvement in outcomes 4.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 has been demonstrated to bind to the ELR -CXC chemokines CXCL4, 9, 10 and 11 (21); however, it is unknown whether CXCR3 is the putative receptor for the ELR -chemokine-mediated inhibition of angiogenesis. CXCR4 is able to bind to CXCL12 and CXCL14 (22,23). As presented in Table I, CXCR7 has been identified as a further receptor for CXCL12 and CXCL11 (24).…”
Section: Features Of CXC Chemokines and Their Receptorsmentioning
confidence: 99%
“…Along with CCR5, it serves as one of the principal coreceptors for HIV entry into leukocytes (3), and is one of the most important chemokine receptors involved in cancer metastasis (4). Stromal-cell derived factor 1 (SDF-1 or CXCL12) was its only known ligand until recently, when CXCR4 was also shown to bind CXCL14 (5) and extracellular ubiquitin (6). Although structures of CXCR4 (7) and CCR5 (8) have been solved with synthetic antagonists, the structural basis for the interaction of CXCR4 (or any other chemokine receptor) with their natural ligands has yet to be determined.…”
mentioning
confidence: 99%